(untitled) (lectio difficilior, 2019)
This article presents the debate about the divine action of YHWH in the metaphor of the נֶשֶׁר (Deuteronomy 32:11). Contrary to the preferred reading (עיר) in exegetical research, this re-vision pleads for עור. For this purpose, a reading, which also recurs to (alleged) ornithological insights, is revealed not as an “old” but as a “new” misunderstanding, rooted in a dualistic construction of gender that finally shortened YHWH. [1]